Transformasi Kurikulum Terhadap Pembelajaran Abad 21 dalam Perspektif Siswa Sekolah Dasar - Muhammad Aqua Mutharik; Arisma Salwa Hilmana (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
This qualitative study, using a phenomenological approach, aims to uncover, study, and deeply understand students' perspectives regarding the curriculum transformation for 21st-century learning they experience in elementary schools. The phenomenological approach was used to explore students' direct experiences as the primary subjects in the learning process, thus gaining a comprehensive understanding of the meaning of curriculum change from their perspectives. Data collection was conducted through in-depth interviews with upper-grade students in elementary schools in Jambi City. The results indicate that the curriculum transformation has a significant impact on students' learning styles, particularly through the implementation of project-based learning that integrates the use of digital technology. This learning model encourages students to be more active, creative, and collaborative in completing learning tasks. Furthermore, student-centered learning makes them the primary actors in the learning process, while teachers act as facilitators. This curriculum transformation also helps develop 21st-century skills, such as critical thinking, communication, collaboration, and digital literacy in elementary school students.